Non-optimal perceptual decision in human navigation. (27th December 2018) - Zhao, Mintao; Warren, William H.
Abstract: We highlight that optimal cue combination does not represent a general principle of cue interaction during navigation, extending Rahnev & Denison's (R&D) summary of nonoptimal perceptual decisions to the navigation domain. However, we argue that the term "suboptimality" does not capture the way visual and nonvisual cues interact in navigational decisions.